Tax bargains: Understanding the role played by public and private actors in influencing tax policy reform in Uganda - Jalia Kangave; Mesharch W. Katusiimeh (United Nations Research Institute for Social Development (UNRISD), 2015)
With the exception of the role played by International Financial Institutions (IFIs) such as the International Monetary Fund, there is little documentation of the role, if any, played by actors other than the state in influencing tax policy reform in Uganda. This paper conducts an investigation into the extent to which actors such as IFIs, members of parliament, the private sector, civil society organizations (CSOs) and non-institutionalized actors write their voices into tax legislation. We also seek to understand the mechanisms used by these actors to influence tax policy reform. Our findings reveal that more organized and economically powerful actors have more opportunities for contributing to the authoring of tax laws. These actors frequently use institutional channels, even though the technologies employed are rarely publicized. There is another group of institutionalized actors (particularly CSOs) who have not traditionally engaged with tax matters but who are increasingly seeking audience in tax debates. CSOs have the potential to influence legislation but their interaction with tax issues is too recent to result in any visible reforms. Non-institutionalized groups for their part use less formal (or extra-legal) means to engage with tax issues. As a result, their bargaining processes are often less coordinated, more reactionary and less sustainable.
Keywords: 330